LEGITIMACY OF INTERNATIONAL COMMERCIAL LAW IN RESOLVING CONSUMER PROTECTION DISPUTES IN E-COMMERCE TRANSACTIONS - Erry Fitrya Primadhany; Azizah (STISIP Widyapuri Mandiri, 2023)
The Development and Progress of Technology in the Era of Globalization Drive Changes in Various Aspects of Life. The rapid advancement of technology provides convenience and flexibility to its users, one of which is in the field of commerce. Alongside the swift technological progress in the world of commerce, society is presented with various transaction systems, one of which is the e-Commerce transaction system. E-Commerce transactions enable the trade of goods/services across borders rapidly and effectively, without the need for direct presence during the transaction. However, in this context, e-Commerce trade transactions inherently possess a high vulnerability to fraudulent activities or actions that could harm consumers. The method employed by the author in this writing is the normative method. The discussion to be examined by the author is how consumer protection in e-Commerce trade transactions and dispute resolution are based on international commercial law. Based on further examination, the conclusion drawn from this writing is that the existence of e-Commerce transactions is regulated by the international trade institution, the United Nations Commission on International Trade Law (UNCITRAL), through the Model Law on Electronic Commerce 1996. Meanwhile, in the event of disputes among parties engaged in e-Commerce transactions across different countries, resolution can be achieved through mutual agreement by the parties, either through litigation or non-litigation methods.